Two new species of the genus Atractoscion, and resurrection of the species Atractoscion atelodus (Günther 1867) (Perciformes: Sciaenidae) - Song, Young Sun; Kim, Jin-Koo; Kang, Jung-Ha; Kim, Seong Yong (Zootaxa, 2017)
A taxonomic re-evaluation of the cosmopolitan fish species Atractoscion aequidens (Cuvier 1830) revealed that it comprises several distinct species occurring in different oceans. Here we describe two new species, Atractoscion macrolepis sp. nov. and Atractoscion microlepis sp. nov., based on specimens collected from Angola and Oman, respectively, and we resurrect the species Atractoscion atelodus (Günther 1867), from Australia. Morphological comparison of A. aequidens from South Africa (type locality) with species from geographically distant localities showed that they differed in the mode number of lateral line pored scales (76 for A. aequidens; 73 for A. macrolepis sp. nov.; 78 for A. microlepis sp. nov.) and the number of dorsal-fin soft rays (26–29 for A. aequidens; 31–33 or 34 for A. atelodus; 24–28 for A. macrolepis sp. nov.; 25–26 for A. microlepis sp. nov.). Comparison of 506 bp sequences in mitochondrial DNA cytochrome c oxidase subunit I showed that the Kimura 2-parameter distance for A. aequidens differs substantially from that for the other species (5.1–5.3% different from A. atelodus; 3.7–4.4 from A. macrolepis sp. nov.; 4.8–5.0 from A. microlepis sp. nov.). The study highlights that DNA barcoding can contribute to confirming the taxonomic status of geographic variations.